2005
DOI: 10.1590/s1415-47572005000100014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of restriction fragment length polymorphism in the kappa-casein gene related to weight expected progeny difference in Nellore cattle

Abstract: Restriction fragment length polymorphism (RFLP) has been detected at the bovine kappa-casein locus. The polymorphism has been analyzed for its effects in cattle production, mostly for milk traits and even for maternal effect on pre-weaning weights. We used polymerase chain reaction -restriction fragment length polymorphism (PCR-RFLP) to genotype 408 Nellore animals for the non-silent mutation (Thr/Ile136 and Asp/Ala148) that characterizes the A and B variants of the polymorphism and compared expected progeny d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Similar results were reported by Silva and Del Lama (1997) who analyzed protein profiles of milk samples from 205 animals of the Guzerat breed, and found a frequency of 0.19 for the variant B. Biase et al (2005) genotyped 408 Nellore animals and found a frequency of 0.09 for the B allele, while Silva and Del Lama (1997) found a frequency of 0.03 in this breed. In the present study, a much higher frequency was reported for the B allele in the Nellore breed (0.18) compared to previous reports.…”
Section: Allele and Genotype Frequenciessupporting
confidence: 85%
“…Similar results were reported by Silva and Del Lama (1997) who analyzed protein profiles of milk samples from 205 animals of the Guzerat breed, and found a frequency of 0.19 for the variant B. Biase et al (2005) genotyped 408 Nellore animals and found a frequency of 0.09 for the B allele, while Silva and Del Lama (1997) found a frequency of 0.03 in this breed. In the present study, a much higher frequency was reported for the B allele in the Nellore breed (0.18) compared to previous reports.…”
Section: Allele and Genotype Frequenciessupporting
confidence: 85%
“…However, high frequency of A allele and AA genotype at k-CN was also observed in Brazilian zebu Gyr and Nellore cattle (Kemenes et al 1999). Biase et al (2005) found an allele frequency of above 0.91 for Allele A in Brazilian Nellore cattle. Similarly, Golijow et al (1999) reported high frequency of A allele in Argentine Creole (AC) and Argentine commercial Holstein (AH) cattle).…”
Section: Resultsmentioning
confidence: 80%
“…Similarly, Golijow et al (1999) reported high frequency of A allele in Argentine Creole (AC) and Argentine commercial Holstein (AH) cattle). The major reason for high frequency of A alleles of k-CN in Brazilian zebu cattle was thought to be due to intensive selection for weight gain and meat production (Biase et al 2005). Conversely, the Indian native cattle breeds like Ladakhi cattle are known to be evolved naturally with almost no artificial selection pressure for productive traits, showed comparatively lower frequency of A allele and AA genotype.…”
Section: Resultsmentioning
confidence: 99%
“…Lara et al 2002 suggest that k-casein variants could have an important role in the growth and maternal effects in beef breeds. However, Biase et al 2005 indicate that a kappa-casein polymorphism did not influence weight-gain in Brazilian Nellore herds, although they found differences in the frequency of the A and B alleles, with the A allele observed most frequently in this beef breed. Similar results were reported by Curi et al 2005 in Nellore, Canchim and a crossbreed (Simmental x Nellore, Angus x Nellore) cattle.…”
Section: Fig 2 Confirmation Of Pcr-rflp For Variants E and H Of K-camentioning
confidence: 81%